The Tumor Suppressor PTEN as Molecular Switch Node Regulating Cell Metabolism and Autophagy: Implications in Immune System and Tumor Microenvironment - Saveria Aquila; Marta Santoro; Annalisa Caputo; Maria Luisa Panno; Vincenzo Pezzi; Francesca De Amicis (Cells, 2020)
Recent studies conducted over the past 10 years evidence the intriguing role of the tumor suppressor gene Phosphatase and Tensin Homolog deleted on Chromosome 10 PTEN in the regulation of cellular energy expenditure, together with its capability to modulate proliferation and survival, thus expanding our knowledge of its physiological functions. Transgenic PTEN mice models are resistant to oncogenic transformation, present decreased adiposity and reduced cellular glucose and glutamine uptake, together with increased mitochondrial oxidative phosphorylation. These acquisitions led to a novel understanding regarding the role of PTEN to counteract cancer cell metabolic reprogramming. Particularly, PTEN drives an “anti-Warburg state” in which less glucose is taken up, but it is more efficiently directed to the mitochondrial Krebs cycle. The maintenance of cellular homeostasis together with reduction of metabolic stress are controlled by specific pathways among which autophagy, a catabolic process strictly governed by mTOR and PTEN. Besides, a role of PTEN in metabolic reprogramming and tumor/stroma interactions in cancer models, has recently been established. The genetic inactivation of PTEN in stromal fibroblasts of mouse mammary glands, accelerates breast cancer initiation and progression. This review will discuss our novel understanding in the molecular connection between cell metabolism and autophagy by PTEN, highlighting novel implications regarding tumor/stroma/immune system interplay. The newly discovered action of PTEN opens innovative avenues for investigations relevant to counteract cancer development and progression.